2018
DOI: 10.3390/su10124541
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Green Investments in Urban Areas: A Proposal of an eco-social-green Model of the City

Abstract: The new and more conscious sensibility towards the environmental sphere supports the idea of “green city”, promotes initiatives of structural integration of the green with the built environment and involves a considerable number of disciplines in a cultural and social debate. The literature reports different experiences of collaborative governance, between administrations and citizens, which tend to enhance the interaction between the different social actors involved in the investments of Green Infrastructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 68 publications
0
33
0
3
Order By: Relevance
“…The multi-functionality in Etna Park highlights the related problems of the choice of location of the various activities in the area and the difficulties of managing such activities within an agricultural environment that assumes a fundamental role for both its traditional productive function and for the environmental and landscape services it provides. These functions are underlined and recognized in the latest community policy guidelines [22,44,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-functionality in Etna Park highlights the related problems of the choice of location of the various activities in the area and the difficulties of managing such activities within an agricultural environment that assumes a fundamental role for both its traditional productive function and for the environmental and landscape services it provides. These functions are underlined and recognized in the latest community policy guidelines [22,44,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that when the rough sets theory is applied to the conservation of resources in Etna Park, the model used provides an excellent eco-eco tool (ecological-economic) [48,54,55] for decision-makers where the application of multi-disciplinary contributions [56] is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The same set of data could also be useful for examining other phases of the public works process, such as design and construction. A further breakdown of the dataset, such as for works on historical buildings [47,48] and on improvement and use of the environment [49] could help to clarify the timeline of the public works process. Lastly, the features affecting the mismatch between the expected and actual costs and times to the completion of public works are worth analyzing, also by comparison with existing literature on the topic.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of the urban adaptation strategies actively involves citizens and other interested stakeholders to favor "non-regret" interventions that can remedy existing problems and bring immediate benefits and socio-economic benefits to increase adaptive capacity and actions based on an ecosystemic or "green" approach [4]. These actions envisaged are aimed to promote experimental interventions of climatic adaptation of public spaces and encourage the diffusion of different forms of GIs and the increase of public and private urban green areas, adopting the logic of green and blue infrastructures, and safeguarding biodiversity in urban areas.…”
Section: The Green Infrastructures As Tools For Climate Adaptation Ofmentioning
confidence: 99%
“…The cities will have an important role to adopt the law and the provisions that are necessary at the various levels but also to ensure the best quality of life in urban areas. Climate impact requires the use of innovative solutions and the rethinking of urban management and planning [4].…”
Section: Introductionmentioning
confidence: 99%